MORPHOMETRIC INDICATORS OF AN ORBIT AT ADULTS IN CONNECTION WITH TYPES OF CRANIUM - Dubyna, S. O. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
The norm of morphometric indicators of bone structures of an orbit for population of 96 people at the age of 48,6 ± 3,2 years without pathology of craniofacial area is established by method of a computer tomography. Means, confidence intervals (р = 0,05), correlation and reliability of distinctions in morphometric indicators of a skull and an orbit by groups on types of cranium are defined. In frequency distribution of the studied population by types of cranium brachiocephalic people are 63 %, dolichocephalic – 27% and mesocephalic – 10 %. In groups by types of cranium among linear indicators of an orbit length of a medial wall statistically reliable decreases from dolichocephals to brachiocephals, length of lateral wall, orbital floor and roof and also orbital breadth – from mesocephals to brachiocephals. Orbital height between groups’ types of cranium reliable does not differ. An angle between medial and lateral walls of orbit statistically reliable increases from dolichocephalic persons to brachiocephalic. The interrelation of changes of an angle of orbital entrance inclination and types of cranium is not observed. The number of statistically significant correlations between morphometric indicators of an orbit increases from dolichocephals to brachiocephals at the absence of a reliable difference between them. Average degree correlation is noted only between orbital breadth and lengths of medial wall and orbital floor; orbital depth and lengths of the orbital floor and roof; between lengths of the orbital floor and roof – at brachiocephals, and also between lengths of the orbital floor and roof – at dolichocephals and mesocephals. The conclusion is drawn that when planning reconstructive operations at bone structures of an orbit it is necessary to consider the available distinctions in length of lateral wall, orbital roof and floor, height and breadth and value of an angle between medial and lateral walls by types of cranium.